INOVASI PELAYANAN “HALO PEMUSTAKA” PASCA PANDEMI COVID-19 DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN PAMEKASAN - Ach. Resa Fachrizi; Abdurahman; Nur Fathin Luaylik; Mohammad Bustanol Husein (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
The service innovation "Halo Pemustaka" is a free pick-up and borrowing service organized by the Pamekasan Regency Library and Archives Service. This study aims to find out how the service innovation "Halo Pemustaka" is implemented to the community. The indicators used are service innovations, namely, saving time, increasing productivity, increasing efficiency, creating convenience and reducing risk. This research uses descriptive qualitative research method. Data collection techniques using documentation, observation, and interviews. Analyzing the data is based on three steps, namely data condensation, data presentation, and conclusion drawing and verification. The results of this study are considered good based on the following indicator aspects: (a) Save time, users can borrow books from home, (b) Increase productivity, service innovation "Halo Pemustaka is declared productive as seen from the enthusiasm of users who increase every month, (c) Increase Efficiency, User saves more energy and transportation costs, (d) Improves convenience, access to service innovation applications "Halo Pemustaka is considered easy and fast, (e) Reduces risk, service innovation "Halo Pemustaka" provides solutions to reduce the risk of corona virus transmission. The "Halo Pemustaka" service innovation carried out by the government through the Pamekasan Regency Library and Archives Service during the Covid-19 pandemic was considered good enough for users but still needs to be improved from every existing service indicator to be even better in the future.